2020
DOI: 10.3390/jcm9113791
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Tear Film Thickness as Measured with OCT and Symptoms and Signs of Dry Eye Disease: A Pooled Analysis of 6 Clinical Trials

Abstract: Purpose: To determine the association between tear film thickness (TFT) as measured with ultra-high resolution optical coherence tomography (UHR-OCT) and signs and symptoms of dry eye disease (DED). Methods: A total of 450 eyes from 225 patients with DED from six different randomized clinical trials were included in this pooled analysis. In all subjects, TFT was measured with a custom-built UHR-OCT system. Symptoms of DED were quantified using a standardized Ocular Surface Disease Index (OSD)I questionnaire an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
(71 reference statements)
0
2
0
2
Order By: Relevance
“…The OSDI is a validated questionnaire that only measures the frequency of dry eye symptoms, but its correlation with clinical signs and tear film parameters is still weak. [24][25][26][27] Garhöfer et al, 28 and Song et al, 29 found weak negative correlation between OSDI score and tear film parameters such as Schirmer and TBUT tests. The higher OSDI score in the hormonal contraceptives group corresponds to its Schirmer and TBUT tests value reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The OSDI is a validated questionnaire that only measures the frequency of dry eye symptoms, but its correlation with clinical signs and tear film parameters is still weak. [24][25][26][27] Garhöfer et al, 28 and Song et al, 29 found weak negative correlation between OSDI score and tear film parameters such as Schirmer and TBUT tests. The higher OSDI score in the hormonal contraceptives group corresponds to its Schirmer and TBUT tests value reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Des Weiteren konnte gezeigt werden, dass die TFT negativ mit dem Ocular Surface Disease Index (OSDI), einem Symptomfragebogen, korreliert und es auch einen signifikanten Zusammenhang zwischen TFT und Schirmer-Test bzw. Tränenfilmaufreißzeit gibt [6,33].…”
Section: Tränenfilmunclassified
“…themenschwerpunkt Die so ermöglichte Schnittbilddarstellung des vorderen Augenabschnittes bietet große Vorteile beispielsweise in der nichtinvasiven Beurteilung kornealer Strukturen [3], des Kammerwinkels [4] oder auch in der Biometrie im Rahmen von Kataraktoperationen [5]. Mit der immer höher werdenden axialen Auflösung ist es in den letzten Jahren gelungen, auch Strukturen des Vorderabschnittes im Bereich von wenigen Mikrometern, wie beispielsweise den Tränenfilm, darzustellen [3,[6][7][8].…”
unclassified
“…Since the early days, in parallel to the spectral domain (Fourier domain) OCT, another class of en face OCT methods have been under development to increase en face imaging speed. Advances in camera technologies and light sources in recent years enabled the rise of en face OCT methods, such as Fourier-domain full-field OCT (FD-FF-OCT), [23][24][25][26] also known as swept-source full-field OCT (SS-FF-OCT), [27][28][29][30] line-field OCT (LF-OCT), [31][32][33][34][35] ultra-high-resolution OCT (UHR-OCT), [36][37][38][39][40][41][42] and so on. An excellent review of en face OCT methods can be found.…”
mentioning
confidence: 99%